LINGUAGEM E ENSINO: SABERES LINGÜÍSTICOS E LITERÁRIOS DOMINANTES EM COMPÊNDIOS ESCOLARES - Zandwais, Ana (Organon, 2003)
The aim of this article is to discuss questions involving principlesof Education during the first and second Republican governmentsin Brazil. We analyse contradictions between the model of educationplanned by workers - the Rationalist School - and the model of educationadopted by the Ministry of Education during the government of GetulioVargas. The results of this research show that as well as the educationalactions, the instruments used by teachers at public schools, such as anthologiesand grammars, only contribute to the reproduction of non- creativeand unqualified pupils.